Spanish - Kraynak, Cecie (--For dummies., 2025)
"Spanish For Dummies gets you started with the Spanish language, even if you've never learned a language before. The trusted Dummies language learning method is quick and practical, so you'll know what to say and do when traveling to a Spanish-speaking country or interacting with Spanish speakers in your community. You'll learn the basics of Spanish grammar and pronunciation, and then you'll explore common phrases you'll need in everyday situations. Get ready to study, work, or travel abroad--or integrate Spanish into your everyday life. This essential resource helps you make small talk, understand common expressions, navigate business settings, ask for directions, go to the doctor, and beyond"--